Pengaruh Model Pembelajaran TGT (Teams Games Tournament) dengan Media Kokami terhadap Kemampuan Berpikir Kritis Siswa - Fitri, Yalin Widia; Ifrianti, Syofnidah; Fiteriani, Ida (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research is motivated by the level of critical thinking abilities of students in class V science subjects at SD N 2 Rejosari which are still considered less critical. The aim of this research is to determine the effect of the Teams Games Tournament (TGT) learning model using Kokami media on students' critical thinking abilities. The research was carried out at SD N 2 Rejosari, Kab. Central Lampung. The type of experimental research used in this research is Quasi Experimental Design. The data collection technique used a quantitative approach by giving questions to 26 class VA students and 19 class VB students. The results of this research indicate that there is an influence of the TGT learning model on critical thinking skills in science subjects. This is proven in hypothesis testing using paired samples t-test data analysis. Based on the results of data analysis, a significance level (sig) < 0.05 was obtained, namely 0.014 < 0.05, which indicates that H0 was rejected and HI was accepted in this study. This means that learning using the TGT learning model has an effect on the critical thinking abilities of class V students at SD Negeri 2 Rejosari Kab. Central Lampung where there are significant differences between the experimental class and the control class.